Susceptibility of soil to wind erosion in arid area of the Central Rift Valley of Ethiopia - Biyensa, Gurmessa; Demissie, Ambachew; Lemma, Bekele (Springer, 2015)
In Central Rift Valley (CRV) of Ethiopia, renewable land resources are under pressure. Acacia woodland clearance, frequent cultivation, crop residue removal and mono-cropping are among the major land mis-management practices in the area. This has largely been affecting the soil quality. The current study is aimed at assessing the impact of Acacia woodland conversion, and the subsequent mis-managements on selected soil physical properties, and their relation to the prevailing wind erosion in the area. For this study, four land use/land cover types, namely protected woodland (PWL), managed pastureland (MPL), parkland agroforestry (PAF) and treeless cropland (TLCL) were considered. Higher (P < 0.001) macro-aggregates (>0.25 mm) fraction of soil was found under PWL and MPL while higher fraction of micro-aggregates (0.053–0.25 mm) of soil was found under PAF and TLCL. Soil under PAF and TLCL had higher (P < 0.001) proportion of aggregates of < 1 mm, implying potential susceptibility of the soil to wind erosion. Higher soil bulk density (BD) was found in the most top layer (0–15 cm) of TLCL and PAF, and this could be attributed to the trampling effect by animals freely released to these land use types. In the study area, conversion of native woodland to PAF and TLCL and the subsequent mismanagements negatively affected some soil physical properties, thereby enhancing severity of soil erosion by wind. In contrast, although not commonly practiced by smallholder farmers, soil under MPL is more stable and less susceptible to wind erosion.